2020
DOI: 10.1016/j.heliyon.2020.e03231
|View full text |Cite
|
Sign up to set email alerts
|

A novel synthesis of new antibacterial nanostructures based on Zn-MOF compound: design, characterization and a high performance application

Abstract: In this study, the novel zinc metal-organic frameworks (MOF) nanostructure has been employed, which was developed using an affordable, environmental friendly, efficient and fast method of ultrasound-assisted reverse micelle (UARM). These nanostructures were identified with various techniques such as FT-IR, XRD, BET, SEM, TG-DSC, TEM and EDS. It was found that the Zn-MOF samples have favorable physicochemical properties. The impact of experimental parameters of the UARM method is effective on the resulting prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…The method for the preparation of Zn‐MOF has already been reported in our previously published work. [ 48 ]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The method for the preparation of Zn‐MOF has already been reported in our previously published work. [ 48 ]…”
Section: Methodsmentioning
confidence: 99%
“…Based on the X-pert high score software, the Zn-MOF powder was indexed to the crystalline system confirmed by the previous study. [48] Figure 5 shows that the XRD patterns of the Zn-MOF are well observed in the nanofibrous Zn-MOF/PVA network, but the intensity is quite reduced. By comparing the XRD patterns of Zn-MOF in this study with the sample in previous study, [52] it can be concluded that Zn-MOF crystalline structure remained intact during the course of synthesis of Zn-MOF/PVA nanofibrous samples.…”
Section: Xrd Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several nanoparticle-based antimicrobials are used against UTIs such as surfactant-based vesicles, nanoemulsions, and polymeric NPs like chitosan NPs [ 51 , 52 ]. Chitosan NPs have the ability to bind with negatively charged bacterial membranes and to increase their permeability.…”
Section: Introductionmentioning
confidence: 99%
“…These methods have advantages including high-speed production, low cost and eco-friendliness. In these methods, products with a variety of structures and different physico-chemical properties can be produced [ 37 , 38 ]. To the best of our knowledge, no study has been conducted on the synthesis of Nano-fertilizers using ultrasonic and microwave method.…”
Section: Introductionmentioning
confidence: 99%